Study of Shoot Multiplication of Strawberry (Fragaria ananassa) (International Journal of Agricultural Research, Innovation and Technology, 2013)
Effects of different hormonal concentration on multiple shoot formation of RABI Strawberry-3 were studied. Where the explants were runner tips that cultured on MS basal medium supplemented with 6-Benzyl Adenine and Kinetin. The maximum percentage 80% of shoot was obtained from Benzyl Adenine concentrations of 0.5 mg/l and 1.0 mg/l whereas Kinetin concentrations were 1.5 mg/l and 2.0 mg/l separately. More promising result was found by combining two impressive concentrations of each hormone. When MS basal media was supplemented with Kinetin 2.0mg/l + Benzyl Adenin A 0.5 mg/l, Kinetin 1.5 mg/l + Benzyl Adenine 0.5 mg/l and Kinetin 1.5 mg/l + Benzyl Adenine 1.0 mg/l respectively then 100% shoots were obtained. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13936 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 69-72, December, 2011